Eras and characters of history - Williams, William R. (Harper, 1882)
Nero and Paul.--The emperor Titus and the apostle John.--Monasticism.--Augustine and Chrysostom.--Buddhism.--Wycliffe, Savonarola, and Huss.--Mahometanism.--The crusades.--Luther and his times.--John Calvin.--John Knox.--The Puritan and the mystic.--Index.